Analisis Faktor-Faktor Yang Mempengaruhi Penggunaan Umpatan di Kalangan Gamers Indonesia - Antares, Kevin Avansa; Darma, Virga Putra (Peneliti.net, 2024)
The use of swearing among Indonesian gamers is a phenomenon that has intensified in recent years along with the rapid growth of the gaming industry and the growing gaming community. This article aims to uncover the factors that influence the use of abusive swearing among Indonesian gamers using a qualitative approach and a sociological perspective. From a sociological perspective, this research adopts social network analysis, symbolic interactionism, and participatory observation to understand the social dynamics within the gaming community. As such, this research provides a deeper understanding of the social and cultural factors that influence swearing behavior in the gaming context. The results of this study are expected to contribute significantly to the understanding of the phenomenon of abusive swearing among Indonesian gamers and assist in formulating effective strategies to address the problem. It is hoped that the insights will encourage efforts to create a more welcoming and ethical gaming environment for all players.